A pilot study of performance among hospitalised elderly patients on a novel test of visuospatial cognition: the letter and shape drawing (LSD) test. (2nd November 2016) - White, D.; Williams, O. A.; Leonard, M.; Exton, C.; Adamis, D.; Hannigan, A.; Cullen, W.; Dunne, C. P.; Meagher, D.
Abstract : Objectives: Conventional bedside tests of visuospatial function such as the clock drawing (CDT) and intersecting pentagons tests (IPT) are subject to considerable inconsistency in their delivery and interpretation. We compared performance on a novel test – the letter and shape drawing (LSD) test – with these conventional tests in hospitalised elderly patients. Methods: The LSD, IPT, CDT and the Montreal Cognitive Assessment (MoCA) were performed in 40 acute elderly medical inpatients at University Hospital Limerick The correlation between these tests was examined as well as the accuracy of the visuospatial tests to identify significant cognitive impairment on the MoCA. Results: The patients (mean age 81.0±7.71; 21 female) had a median MoCA score of 15.5 (range=1–29). There was a strong, positive correlation between the LSD and both the CDT ( r =0.56) and IPT ( r =0.71). The correlation between the LSD and MoCA ( r =0.91) was greater than for the CDT and IPT (both 0.67). The LSD correlated highly with all MoCA domains (ranging from 0.54 to 0.86) and especially for the domains of orientation ( r =0.86), attention (0.81) and visuospatial function ( r =0.73). Two or more errors on the LSD identified 90% (26/29) of those patients with MoCA scores of ⩽20, which was substantially higher than for the CDT (59%) and IPT (55%). Conclusion: The LSD is a novel test of visuospatial function that is brief, readily administered and easily interpreted. Performance correlates strongly with other tests of visuospatial ability, with favourable ability to identify patients with significant impairment of general cognition.